STATE AND PROBLEMS OF GEOLOGICAL BRANCH OF UKRAINE - GURSKY , D.; KALININ, V.; GEYCHENKO , M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
One of component of strategic line of interior state internal policy of Ukraine is the raising of geological branch for the purpose ofprospecting and exploration fresh mineral deposits. At last decades was increased exploration work for non-traditional deposits(copper, lead, zink, molybdenum, vanadium, gold, rare elements etc). It was developed state program of expansion of priority lines ofgeological investigations for the purpose of supplying Ukraine economy with own scarce resources. Geological branch interested inhigh-skilled personnel training.